THE ROLE OF A FOREIGN LANGUAGE IN THE DEVELOPMENT OF THE HUMANITARIAN CULTURE OF PERSONALITY - Telichko, Victoria (Mountain School of Ukrainian Carpaty, 2022)
The article is devoted to the consideration of the process of learning a foreign language as an effective means of personal social and humanitarian development of students. It is substantiated that the orientation of the Ukrainian education system to enter the world educational space determines the tendency to update foreign language education. It is a question of rethinking the purposes, the maintenance, principles and methods of training of a foreign language for the purpose of achievement of personal results of training which promote development of humanitarian culture of the person. The purpose of the study - based on the study of theory and practice of foreign language education to consider the potential of a foreign language in the development of humanitarian culture of the individual. Within the limits of research theoretical methods are used: a method of the analysis and synthesis, a method of the theoretical analysis of scientific literature on a problem of development of humanitarian culture of the person and foreign language education. Based on the analysis of the scientific literature, the humanities culture is considered as an integral characteristic of a socially mature personality based on the enrichment of its value-semantic, cognitive, communicative, moral-aesthetic, reflective spheres of personality in the process of its social development. It is established that a foreign language performs communicativepragmatic, cognitive, humanistic and personal-formative functions. It contributes to the development of humanitarian culture of the individual in a set of characteristics such as communication, cognitive independence, artistic and aesthetic receptivity, empathy, social subjectivity based on humanistic values that ensure effective communication and positive self-realization in all spheres of activity. It is generalized that humanitarian culture performs a socializing function, is the main element of involvement of the individual in the conditions and norms of existence in society and the most important component of the process of harmonious social development of the individual. Prospects for the study of the problem are related to the creation of educational and methodological complexes in a foreign language on a broad interdisciplinary basis, the development of scientific principles of humanitarian examination of modern educational and methodological complexes in a foreign language for their humanitarian potential. Keywords: humanitarian culture, foreign language, foreign language education, spheres of personality, socially valuable qualities.